Characterization of Flocs in Dewatering of Coal Plant Tailings - Can Gungoren; Safak G. Ozkan; Yasin Baktarhan; Ilgin Kursun; Orhan Ozdemir (Hittite Journal of Science and Engineering, 2018)
Flocculation is a widely used method for dewatering fine coal tailings. Flocs must resist to the shear stresses during the following processes such as flotation, cyclone separation, and pumping. Therefore, the strength of the flocs must be considered during flocculation. In this study, the fine coal tailings were dewatered with an anionic flocculant SNF-923 at various dosages, and the floc size of the coal tailings was characterized using a laser diffraction particle size analyzer with respect to time in order to determine the change in the floc size and hence the floc strength. The results of this study clearly indicated that the determination of the floc size with a laser particle size analyzer could be a simple and good method to observe the flocculation efficiency in terms of the floc strength.